Increasing perceived health and mental health literacy among separated refugee Ukrainian families with urgent needs occasioned by invasion—a group intervention study with participatory methodology in Sweden - Ekblad, Solvig; Gramatik, Oksana; Suprun, Yuliia (Frontiers in Public Health, 2024)
Background With the increasing numbers of refugees from Ukraine affected by the ongoing war, there is a high risk of trauma-related stress due to low local health and mental health literacy care. Perceived good health is a human right. Earlier studies show that intervention for refugees can reduce and prevent post-migration stress and anxiety. The present explorative study aimed to investigate the feasibility and effectiveness of a short, trauma-focused group intervention (in Swedish “hälsoskola”) for Ukrainian-speaking refugees (EU’s mass refugee directive). This intervention was part of an ESF project aiming to get the subjects closer to the labor market in Västernorrland County, Sweden. Materials and methods A mixed-methods design, a participatory methodology, and an evaluation were used. Data were obtained with a short questionnaire in Ukrainian. It included a visual analogue health-rating scale, an observation, and an oral evaluation in groups. For practical and ethical reasons, there was no control group. Each group met five times for 2 h, a total of 10 h excluding pre- and post-assessment. There were eight sets of five group sessions per set, a total of 40 sessions. Brief initial and concluding breathing exercises sought to reduce stress among the participants. Results Baseline data were obtained from 99 participants, mostly females. Data gathered directly after the group intervention from 57 participants who had filled in both the pre- and post-questionnaires showed that (1) perceived anxiety/stress was significantly reduced (chi-2 25,53, df = 4, p < 001). (2) The participants showed significantly better perceived health as assessed on a visual analogue scale (average change from 63.16 to 71.18, p < 0.001). This result was supported by the participants’ questions, which were qualitatively evaluated using thematic content analysis. Five general themes stemmed from questions raised in dialogue with the participants plus observation with the respective local expert. The participants received answers to their questions, and their perceived negative attitudes to authorities changed to more positive ones. Conclusion By dialogue between the participants’ needs of knowledge and direct answers by the local expert, respectively, was feasible and effective as they perceived trust and health and mental health literacy increased. Implications for primary prevention are discussed.